Antibodies against dengue virus in patients with dislipidemias - Jennifer Gotera; Nereida Josefina Valero-Cedeño; Ayari Avila-Leal; Johan Linares; Jesús Mosquera; Valmore Bermúdez; Teresa Veliz (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2019)
The objective was to compare the antibodies against the dengue virus in patients with different types of dyslipidemias. Type of descriptive, prospective study of non-experimental, crosssectional design. The sample consisted of 214 individuals, distributed in 169 with dyslipidemias and 45 controls. Serum lipids and anti-dengue antibodies were determined by conventional biochemical and immunological methods. They were classified into 3 groups: hypertriacilgliceridemia (279.7 ± 84.2 mg / dl); hypercholesterolemia (252.7 ± 38.5 mg / dl) and the group with high triglycerides and cholesterol (257.3 ± 38.5, 271.6 ± 88.7 mg / dl). 96% of the patients showed immunity (IgG) against dengue virus, the primary response (IgM) was present in 22%. Regarding the positivity of IgM, the highest frequency was in the group with hypertriacilgliceridemia (34.2%), while the frequency for IgG was in the group with triacylglycerides and high cholesterol (31.2%). In this study, no difference was observed between IgG and IgM antibodies against dengue virus in patients with dyslipidemia and the control group. Future studies are needed to demonstrate in areas of lower endemicity for the dengue virus if, in fact, the alteration of the lipid profile modifies the intensity of response to the infection.